2020
DOI: 10.1111/joim.13097
|View full text |Cite
|
Sign up to set email alerts
|

2D shear wave elastography combined with age and serum biomarkers prior to kasai surgery predicts native liver survival of biliary atresia infants

Abstract: Background. The prognosis of patients with biliary atresia (BA) after Kasai portoenterostomy (KPE) varies, and precisely predicting the outcomes of KPE before surgery is still challenging. Methods. A total of 158 patients who underwent KPE in our hospital were included in this study. The patients in the training cohort were recruited from January 2012 to October 2017 (n = 118), and then, those in the validation cohort were recruited from November 2017 to April 2019 (n = 40). Combined nomogram models were devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…The observed correlation of the native liver survival rates with the age at surgery is consistent with the literary data on this subject [11,13,16,19]. For instance, Wang et al demonstrated that Kasai surgery at the age of under 81 days significantly increases native liver life expectancy as compared with the patients operated at a later age [13]. In a large-scale multicenter study carried out in France with the enrollment of 1044 patients during the 1986-2009 period, the 5-, 10-, and 20-year native liver survival rates constituted 40%, 36%, and 30%, respectively [16].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The observed correlation of the native liver survival rates with the age at surgery is consistent with the literary data on this subject [11,13,16,19]. For instance, Wang et al demonstrated that Kasai surgery at the age of under 81 days significantly increases native liver life expectancy as compared with the patients operated at a later age [13]. In a large-scale multicenter study carried out in France with the enrollment of 1044 patients during the 1986-2009 period, the 5-, 10-, and 20-year native liver survival rates constituted 40%, 36%, and 30%, respectively [16].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we assessed the effectiveness of Kasai surgery by post-operative resolution of BA symptoms, age-related complications, and survival rates. According to the published evidence, the effectiveness of Kasai surgery generally varies in the range of 50-95% [10][11][12][13][14][15][16]. In some studies, the effectiveness is assessed by a decrease in bilirubin levels to 2 mg/dL (34.2 µmol/L), which renders the effectiveness of 40% on average [15].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that survival rates for the < 1 year-olds showed no correlation with the age at Kasai surgery (Figure 3). The observed correlation of the native liver survival rates with the age at surgery is consistent with the literary data on this subject [11,13,16,19]. should be considered as an echo of deteriorating changes that would rapidly progress in the absence of timely surgical intervention (and this point is consistent with our observations for the cases of ineffective surgery).…”
Section: Survival Studysupporting
confidence: 91%
“…For instance, Wang et al have demonstrated that Kasai surgery at the age under 81 days significantly increases the native liver life expectancy as compared with the patients operated at later age[13]. In a large-scale multicenter study carried out in France with the enrollment of 1044 patients during 1986-2009 period, the 5-, 10-, and 20-year native liver survival rates constituted 40%, 36%, and 30%, respectivelyError!…”
mentioning
confidence: 99%
“…An accurate method to monitor the progression of liver fibrosis can lead to better prognosis and management of pediatric patients with chronic liver diseases [ 1 2 ]. For example, in patients with biliary atresia (BA), the stage of fibrosis at the time of Kasai hepatoportoenterostomy (KPE) can influence the outcomes [ 3 4 ]. Although liver biopsy is still considered the reference standard for diagnosing and staging liver fibrosis in children, its limitations [ 5 ] (e.g., invasiveness and interobserver and sampling variability) are well known.…”
Section: Introductionmentioning
confidence: 99%